Conflict Between Domestic Reindeer and Their Wild Counterparts: A Review of Eurasian and North American Experience - Klein, David R. (ARCTIC, 1980)
Experience in the Soviet Union and Alaska indicates that the major potential conflicts between domestic reindeer and their wild counterparts (both caribou and reindeer are of the same species, Rangifer tarandus) are: (1) Loss of domestic reindeer to wild herds. Although this can be reduced under close herding, it is still a serious problem wherever wild reindeer or caribou and domestic reindeer coexist. Domestic reindeer joining wild herds appear to have low breeding success and therefore probably have little genetic influence on the larger wild populations. (2) Competition for forage between domestic reindeer and wild herds, which is primarily restricted to the winter range. Herded reindeer feed more intensively than the wild, free-ranging animals and therefore their effect on range forage is greater. (3) Diseases and parasites may be readily transmitted between domestic reindeer and their wild counterparts. However, most diseases and parasites common to the species are endemic to both wild and domestic herds.